Physiological and production responses of intensively managed Ostriches to L-Carnitine - Casey, N.H. (Norman Henry) (University of Pretoria, 2015)
This set of experiments evaluated the physiological responses of intensively managed ostriches to L-carnitine. In experiment 1, 32 female and 16 male Zimbabwean Blue Neck and South African Black Neck breeders (n=48 of each sub-species; eight years old), were investigated in 16 breeder units of two females and one male (Trio), in a completely randomised design within four treatments and four replicates over an 8-month period during the breeding season. The same basal diet was fed supplemented with 0 (T0, control), 125 (T125), 250 (T250) or 600 (T600) mg/kg L-carnitine. T600 improved the egg production percentage, egg fertility percentage and the hatchability of set eggs for Black-Necks and Blue-Necks, respectively, and the hatchability of fertile eggs in Black Necks. L-carnitine did not affect egg shape index, defective eggs, egg weight, embryonic and post-hatch mortality. In experiment 2, 12 Black Neck males (5.5 years old) were allocated to three treatments (T0, T250 and T500) and four replicates. Semen samples were collected once a month over three months. L-carnitine had a significant effect on semen volume, sperm motility, live sperm percentage and sperm count, but had no significant effect on abnormal sperm percentage. In experiment 3, 32 day-old Black Neck ostrich chicks were allocated to treatments T0, T125, T250 and T600 with four replicates of two chicks. Chicks were vaccinated against inactive Newcastle Disease (ND) vaccine at day 30 as primary, and at day 51 as booster immunisation. ND antibody responses in the sera were monitored over three phases at 51, 70 and 80 days. Anti-NDV antibodies were detected using a modified chicken anti-NDV enzyme-like immunosorbent assay (ELISA). The treatments and the time periods and their interactions influenced ND antibody responses. T125 and T250 had the highest level of ND antibody response compare to the other groups. There were no differences in ND antibody response between T0 and T600 as well as T125 and T250. The highest ND antibody responses were recorded at day 70. Experiment 4 was designed the same as 3, to determine chicks’ growth responses over the 60-day period. Live weight and live weight gain values of T125 and T250 did not differ from those of T0. T600 had the lowest feed conversion ratio (FCR) during the total period. Feed intake (FI) was reduced in the T125 and T600 treatments compared to T0 and T250 over the total period. T125 gave the lowest FI and FCR responses over the total period, whereas there was no difference between T0 and T250. These results suggest that dietary T600 can have a beneficial effect on egg production, fertility and hatchability in the Black and Blue Neck breeders and T250 might improve sperm quality in males. In ostrich chicks T125 and T250 had positive effects on immune responses and T125 can improve the performance by decreasing the FCR. In contrast, the suppressive effect of a high inclusion level (T600) might indicate that ostrich chicks are sensitive to high inclusion levels that could cause adverse effects.